Band gap, piezoelectricity and temperature dependence of differential permittivity and energy storage density of PZT with different Zr/Ti ratios. (October 2018) - Samanta, Shibnath; Sankaranarayanan, V.; Sethupathi, K.
Abstract: Pb (Zr, Ti)O3, (PZT) with Zr/Ti ratio 36/64, 44/56, 52/48, 60/40 and 68/32 are prepared to study the dependence of band gap, energy storage density and differential permittivity on Zr/Ti ratio. Band gaps of the samples are calculated by Kubelka-Munk plots from the Diffuse Reflectance Spectroscopy. The nature of the dependence of band gap on Zr/Ti ratio follows a theoretical model. Comparative studies on the dielectric, ferroelectric and piezo-electric properties are performed. Differential permittivity (DP) is calculated in the temperature range, 30 °C–200 °C. The DP is found to depend strongly on the electric field, temperature and Zr/Ti ratio. Similarly, the change in recoverable energy storage density ( ΔJ ) with temperature and Zr/Ti ratio is also investigated systematically. At room temperature, the value of ΔJ is observed to be as high as 64.4 mJ/cm 3 at an applied field of 30 kV/cm for PZT (36/64) sample. The value of ΔJ decreases with Zr-content and increases with temperature up to 200 °C (experimental limitation) for PZT (36/64), PZT (44/56) and PZT (52/48) whereas the value stops increasing around 190 and 180 °C for PZT (60/40) and PZT (68/32). The highest value of ΔJ is observed to be 172.23 mJ/cm 3 at 200 °C for PZT (36/64). Highlights: Nature of change in band gap with Zr/Ti around MPB follows a theoretical model. Structural transformation and enhancement of properties at MPB are observed. Differential permittivity attains maximum at certain temperature and electric field. Energy storage density increases with temperature up to certain temperatures. Changes in both of these with Zr/Ti ratio are different at different temperature.